Anti-fouling and highly permeable thin-film composite forward osmosis membranes based on the reactive polyvinylidene fluoride porous substrates - Li, Manman; Yang, Yuling; Zhu, Lijing; Wang, Gang; Zeng, Zhixiang; Xue, Lixin (Colloids and surfaces. A, Physicochemical and engineering aspects, 2022)
Currently, thin-film composite (TFC) forward osmosis (FO) membranes are widely developed for wastewater purification, although it is a pressing subject to further improve its permeability, selectivity, and fouling resistance. Here, the polyvinylidene fluoride (PVDF) membranes were modified with dopamine (DA) and polyethyleneimine (PEI) via surface segregation during non-solvent induced phase separation (NIPS). And then some residual amine groups on the as-prepared PVDF/DA-PEI membranes participated in the reaction with 1,3,5-benzenetricarboxylic acid chloride (TMC) by interfacial polymerization (IP), forming the TFC FO membranes. Furthermore, they were co-deposited by tannic acid (TA) and taurine, engineering the tTFC FO membranes. The introduction of DA and PEI in the substrate enhances the selectivity of the membrane having a low specific reverse solute flux (Js/Jw), and the TA-taurine layer improves the anti-fouling of the surface. Especially, tTFC6 (6 represents the weight concentration of DA and PEI in the substrate) has an excellent performance has a large Jw of 42.10 ± 0.86 L m−2 h−1, a low Js/Jw of 0.06 ± 0.02 g/L, and a high flux recovery (FRR) of more than 90% using bovine serum albumin (BSA), sodium alginate (SA), and SiO2 nanoparticles as model contaminants. The results provide new insights into the preparation of highly permeable and anti-fouling FO membranes. [Display omitted]